MODELING AND EVALUATION OF INTERNATIONAL RESERVES DETERMINANTS IN UKRAINE - Hrytsyshyn , A. T. (The actual problems of regional economy development, 2020)
The article deals with the process of international reserves management in Ukraine, in particular, with the modeling of the main determinants of reserve assets in the country. Based on the analysis of empirical studies of factors influencing the volume and dynamics of reserve assets, six main groups of determinants of international reserves have been identified, namely: size and level of economic growth, current account of balance of payments, capital account of balance of payments, exchange rate volatility, opportunity cost of international reserves and institutional factors. Based on this classification, a regression analysis of the main determinants of international reserves in Ukraine during 1993–2018 has been conducted. The econometric study has found a direct and significant impact of such indicators as the average propensity to export, the average propensity to import, the ratio of foreign direct investment to GDP and the Joneses index. The inverse and significant impact of the opportunity cost of international reserves has also been established. Such indicators as GDP per capita and real effective exchange rate have been found to be statistically insignificant factors influencing reserves in Ukraine.The following methods have been used in the study: descriptive-analytical and statistical-economic method – to construct statistical and analytical tables; modeling and formalization – to construct models of factors influencing international reserves; regression analysis – to verify the validity of models of factors influencing international reserves; comparative analysis – to compare the results of the study.